2013
DOI: 10.1155/2013/315429
|View full text |Cite
|
Sign up to set email alerts
|

Eating Problems and Overlap with ADHD and Autism Spectrum Disorders in a Nationwide Twin Study of 9‐ and 12‐Year‐Old Children

Abstract: Aim. To establish the prevalence of restrictive eating problems, the overlap and association with attention-deficit/hyperactivity disorder (ADHD), and autism spectrum disorders (ASD) and to estimate the heritability of eating problems in a general population sample of twins aged 9 and 12. Methods. Parents of all Swedish 9- and 12-year-old twin pairs born between 1993 and 1998 (n = 12,366) were interviewed regarding symptoms of ADHD, ASD, and eating problems (EAT-P). Intraclass correlations and structural equat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(59 citation statements)
references
References 33 publications
2
54
3
Order By: Relevance
“…Outcomes for 33,417 individuals (ADHD = 4,013/Controls = 29,404), across 12 retained studies were available. Most paediatric studies measured symptoms such as LOC, binge eating episodes or restrictive behaviors, whereas all adult studies reported on syndromes (AN, BN, and BED). Two studies were considered outliers since their effect size had a wide confidence interval that had an upper bound that was much bigger than all others, and were excluded from the analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Outcomes for 33,417 individuals (ADHD = 4,013/Controls = 29,404), across 12 retained studies were available. Most paediatric studies measured symptoms such as LOC, binge eating episodes or restrictive behaviors, whereas all adult studies reported on syndromes (AN, BN, and BED). Two studies were considered outliers since their effect size had a wide confidence interval that had an upper bound that was much bigger than all others, and were excluded from the analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Conversely, when the prevalence of ADHD was investigated in ED, studies in AN patients found rates ranging from 3% up to 16.2%, while for BN patients it ranged from 9% up 34.9%, and for BED patients it was 19.8% . The positive association of ADHD and ED traits has also been demonstrated in correlational studies, with a correlation coefficient ranging from 0.23 to 0.59 . The number of ADHD symptoms correlate with ED symptom severity in all binge/purge ED subtypes .…”
mentioning
confidence: 90%
“…Thus, the aim of this prospective single-centre study in very low birth weight (VLBW) infants was to systematically assess the incidence of nonneurological side effects in VLBW infants receiving systemic steroids. HCM was suspected on clinical findings and confirmed on echocardiography (3). Echocardiography/ultrasonography was performed on days 1, 2, 3, 5 and 7, then at least weekly.…”
Section: Dear Sirmentioning
confidence: 99%
“…Over half of the studies 17,24,25,35,55,58 reported no association between age and disordered eating; four studies 18,21,22,59 found that prevalence increased with age; and four studies 27,28,53,57 found more disordered eating in children of younger age. Overall, there were no convincing associations between age and disordered eating.…”
Section: Parental and Child Characteristics Related To Early-onset DImentioning
confidence: 98%